A Systematic Review of Center of Mass as a Measure of Dynamic Postural Control Following Concussion - Sarah Patejak; Joshua Forrest; Emily Harting; Mable Sisk; Eric Schussler (International Journal of Sports Physical Therapy)
# Background The incidence of sports-related concussion in the US is between 1.6-3.8 million annually. Identification of ongoing impairment post-concussion continues to be challenging, as research indicates many patients are cleared for return to activity while still suffering subclinical impairment of function. Purpose: To identify and review the current literature on the use of center of mass (COM) during gait as a potential indicator variable after concussive injury. Study Design: Systematic Review